Fibre-based devices for optical subsystem applications - Shum, Ping (2008)
Optical fibre-based devices are attractive in various areas, due to their immunity to electromagnetic interference, high sensitivity, compactness and simplicity of fabrications. Fibre-based devices, such as fiber long period grating (LPG) and fiber Bragg grating (FBG), are becoming more popular and widely recognized as significant optical components in the field of optical subsystem because their usefulness in producing various spectra in the optical domain. By modulating the refractive index and pitch length inside the fiber core, the gratings will result in various reflection and transmission spectra which are useful for many applications in optical subsystem, e.g., sensing system.